A Simple Screening Tool to Predict Outcomes in Older Adults Undergoing Emergency General Surgery. Issue 2 (9th October 2018) - Zattoni, Davide; Montroni, Isacco; Saur, Nicole Marie; Garutti, Anna; Bacchi Reggiani, Maria Letizia; Galetti, Caterina; Calogero, Pietro; Tonini, Valeria
Abstract : Objectives: To determine whether the Flemish version of the Triage Risk Screening Tool (fTRST) can be used to accurately assess frailty in an emergency setting. Design: Prospective observational study. Setting: of a tertiary referral hospital. Patients: All individuals aged 70 and older consecutively admitted to the emergency surgery unit with an urgent need for abdominal surgery between December 2015 and May 2016 who met inclusion criteria (N=110). Measurements: Individuals were screened with the fTRST and additional metrics such as the age‐adjusted Charlson Comorbidity Index and American Society of Anesthesiology score. Thirty‐ and 90‐day postoperative complications where recorded. Regression analyses were performed to identify possible preoperative predictors of adverse outcomes. Results: Thirty‐day major complications (Clavien‐Dindo Classification 3–5) occurred in 28.2% of participants (n=31). fTRST had the highest correlation with major complications (odds ratio (OR) = 7.42). All participants who died within 30 days of surgery has a fTRST score of 2 or greater (area under the receiver operating curve (AUC)=71.3). When risk factors for overall 90‐day mortality were analyzed, a fTRST score of 2 or greater had sensitivity of 96% (95% confidence interval CI=79.6–99.9%), specificity of 43.5% (95% CI=32.8–54.7%) (AUC=69.8%; OR=18.50, 95% CI=2.39–143.11, p = .005). The average length of hospital stay was more than twice as long in the group with a fTRST score of 2 or greater (15.2 days) than in those with a score less than 2 (6.6 days) (p = .005). Conclusion: The fTRST is an effective tool to predict mortality, morbidity, and length of stay after emergency surgery and can therefore be used to anticipate postoperative course, determine care goals, and plan for involvement of a dedicated geriatric care team.J Am Geriatr Soc 67:309–316, 2019.